Analysis of Equity in Access to Cataract Surgery Services Among BPJS Kesehatan Participants - Ikhsan, M; Hasibuan, Syarif Rahman; Widyasanti, Nisrina; Utomo, Wahyudi; Akbar, Taufik (Jurnal Manajemen Pelayanan Publik, 2026)
Cataract is the leading cause of avoidable blindness worldwide, yet equitable access to surgery remains a challenge despite universal health coverage. This study examines equity in cataract surgery utilization among participants of Indonesia’s national health insurance program using logistic regression and a multilayer perceptron (MLP) model. Findings show that age, sex, marital status, place of residence, and insurance segment are significantly associated with surgery utilization. Male participants, older age groups, and certain insurance segments are more likely to undergo surgery, indicating structural inequities in access. These findings underscore the need to strengthen referral mechanisms, reduce access barriers, and improve public service management policies within JKN to advance equity in essential eye care services.